The Role of Negotiation: Negotiated Justice? - Macduff, Ian (Victoria University of Wellington Law Review, 1995)
The article comments on a number of papers presented at the "Treaty Claims: The Unfinished Business" Conference. It discusses a number of aspects of the role of negotiation, both in general terms and in the specific area of Treaty claims. The author does so in the framework established in the awareness that negotiation, dispute resolution, bargaining, are not only practical and instrumental activities but also cultural, meaningful acts. If this is the case, people bargain not only about material things about tangible results, but also about identity. The author discusses issues raised by the proposals raised for the Treaty settlement process and the Conference, arguing that the most important purpose of the negotiations is the protection and management of the negotiation process itself. This article also includes a question and answer session with Professor Macduff.